Vocational Teacher Education in Central Asia: Developing Skills and Facilitating Success - Thomas Köhler (Technical and Vocational Education and Training: Issues, Concerns and Prospects, 2018)
This open access volume presents papers on vocational education, project-based learning and science didactic approaches, illustrating with sample cases, and with a special focus on Central Asian states. Thematically embedded in the area of Technical Vocational Education and Training (TVET), the book examines the following main topics: project-based learning (PBL), specific didactics with a linkage to food technologies and laboratory didactics, media and new technologies in TVET, evaluation of competencies including aspects of measurement, examination issues, and labour market and private sector issues in TVET, and research methods with a focus on empirical research and the role of scientific networks. It presents outcomes from TVET programmes at various universities, colleges, and teacher training institutes in Central Asia.